Sulfur vacancy-rich CdS loaded on filter paper-derived 3D nitrogen-doped mesoporous carbon carrier for photocatalytic VOC removal. Issue 6 (9th May 2018) - Wang, Lusha; Xu, Xinxin; Wang, Yun; Wang, Xinjiao; Shi, Fa-nian
Abstract : A new strategy is explored to fabricate a sulfur vacancy-rich CdS composite photocatalyst with a nitrogen-doped 3D porous carbon matrix for VOC removal. Abstract : A simple method is developed for the synthesis of a sulfur vacancy-rich CdS-based composite photocatalyst with a three-dimensional nitrogen-doped mesoporous carbon matrix using a Cd(ii )-based coordination polymer and filter paper as precursors. Using this strategy, an excellent composite photocatalyst (CdS@3D-NPC ) is synthesized successfully, in which CdS nanoparticles with a small size (about 6 to 8 nm) are distributed homogenously in the three-dimensional nitrogen-doped mesoporous carbon matrix. During calcination, some coordinated nitrogen atoms from the organic ligands occupy the sites of S 2− and dope in the lattice of CdS, which produces abundant sulfur vacancies. These sulfur vacancies promote the transportation of photogenerated electrons and their separation from photogenerated holes, which enhance the photocatalytic activity of the composite material.CdS@3D-NPC shows a promising performance for the decomposition of volatile organic compounds (VOCs), such as formaldehyde and benzene gas. The stability and durability ofCdS@3D-NPC are outstanding. Its VOC removal efficiency remains as high as 95% of the original value after five continuous cycles of photocatalytic reaction for 30 h. The mechanism study illustrates that the excellent VOC removal performance originates from the synergetic effect of sulfur vacancies and excellent conductivity of the three-dimensional nitrogen-doped mesoporous carbon matrix. We anticipate thatCdS@3D-NPC will be employed as an ideal tool for indoor air purification.